A new approach towards giant cell arteritis - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Giant cell arteritis is a rare systemic vasculitis affecting large- and medium-sized arteries. Focal arteries lesions, include mononuclear cells infiltration of the vessel wall with giant cell formation. It is a disease of elderly persons and can result in a wide variety of systemic, neurological and ophthalmic complications, due to ischemia. The incidence of visual loss and ocular involvement varies between 14-88%, but one of the most common and severe complications is anterior ischemic optic neuropathy. The other ocular ischemic lesions include: central retinal artery occlusion, choroidal ischemia, diplopia, ocular motor paresis, anterior uveitis, cataract, ocular hypotony, corneal oedema and ulcerations, episcleritis and anterior scleritis, orbital cellulitis and pseudotumor. Because giant cell arteritis is potentially blinding disease, early diagnosis and immediate treatment with high dose corticosteroids may prevent further damage to the affected eye and prevent visual loss in the opposite eye. The purpose of this review is to revise established knowledge and to highlight the recent developments in diagnosis and management of giant cell arteritis.